Longitudinal Study on Low-Dose Aspirin versus Placebo Administration in Silent Brain Infarcts: The Silence Study - Ilaria Maestrini; Marta Altieri; Laura Di Clemente; Edoardo Vicenzini; Patrizia Pantano; Eytan Raz; Mauro Silvestrini; Leandro Provinciali; Isabella Paolino; Carmine Marini; Matteo Di Giuseppe; Tommasina Russo; et al. (Stroke Research and Treatment)
Background. We investigated low-dose aspirin (ASA) efficacy and safety in subjects with silent brain infarcts (SBIs) in preventing new cerebrovascular (CVD) events as well as cognitive impairment. Methods. We included subjects aged ≥45 years, with at least one SBI and no previous CVD. Subjects were followed up to 4 years assessing CVD and SBI incidence as primary endpoint and as secondary endpoints: (a) cardiovascular and adverse events and (b) cognitive impairment. Results. Thirty-six subjects received ASA while 47 were untreated. Primary endpoint occurred in 9 controls (19.1%) versus 2 (5.6%) in the ASA group (p=0.10). Secondary endpoints did not differ in the two groups. Only baseline leukoaraiosis predicts primary [OR 5.4 (95%CI 1.3-22.9, p=0.022)] and secondary endpoint-a [3.2 (95%CI 1.1-9.6, p=0.040)] occurrence. Conclusions. These data show an increase of new CVD events in the untreated group. Despite the study limitations, SBI seems to be a negative prognostic factor and ASA preventive treatment might improve SBI prognosis. EU Clinical trial is registered with EudraCT Number: 2005-000996-16; Sponsor Protocol Number: 694/30.06.04.